THE IMPACT OF LEARNING MODELS PROBLEMS-BASED LEARNING IN STUDENTS' SCIENCE LEARNING OUTCOMES AT SDN 3 RAJABASA BANDAR LAMPUNG CITY: Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Ipa Peserta Didik Kelas IVA di SD Negeri 3 Rajabasa Kota Bandar Lampung - Pratama, Febri (EDUCATE, 2024)
Lack of student involvement in science learning activities causes learning outcomes to be less than optimal. This study aims to analyze the effect of the Problem Based Learning (PBL) learning model on science learning outcomes of grade IV elementary school students. The study used a quantitative experimental method, pre-experimental design with a one group pretest-posttest form. The study was conducted for 2 months in grade IV of State Elementary School 3 Rajabasa, Bandar Lampung City. The population of the study was all grade IV students at State Elementary School 3 Rajabasa, Bandar Lampung City. The sample used in this study was all grade IV students at the elementary school. Data collection technique with 25 multiple choice questions, with cognitive development levels C4 and C5 on plant structure and function and plant parts. Data were analyzed using paired sample t-test. The conclusion of the study shows that the PBL learning model can improve the learning outcomes of grade IV elementary school students, with a significance value (2-tailed) of 0.00 <0.05.